Investigating chromatin folding and fibre-fibre formation - Lee, Kwok Kin (2014)
Post translational modifications (PTMs) on histone tails are commonly denoted marks of repression or activation in terms of their link to gene silencing or activation. One of the ways in which PTMs serves their gene regulation function is by altering chromatin compaction. In this study, the intra- and inter-nucleosomal array interactions containing PTMs, tri-methylation on H3 lysine9 (H3K9me3) and di-methylation of H4 lysine20 (H4K20me2), are investigated. Results show that although H3K9me3 is a mark of repressive heterochromatin, H3K9me3 alone does not appear to contribute to the tightly folded conformational characteristics of heterochromatin. Conversely, the H4K20me2 modification gives rise to highly compacted arrays in salt-induced compaction conditions, suggesting a role in maintaining chromatin structural framework.